Method for preparing iron-containing furnace charge through vacuum extrusion forming and low-temperature consolidation

By combining fine grinding activation and vacuum extrusion molding with low-temperature consolidation, the problems of poor performance of finished lumps and long consolidation time in the cold pressing process were solved, and efficient molding and rapid consolidation of iron-containing furnace charges were achieved, which improved the strength and reduction performance of the lumps and reduced fossil energy consumption.

CN120796700APending Publication Date: 2025-10-17CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410613188.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

When preparing iron-containing charge for blast furnaces, the existing cold-pressed briquetting process produces poor performance of the finished briquette, takes a long time to solidify, or introduces many impurities, making it difficult to meet the large-scale production needs of the modern steel industry.

Method used

The combined technology of fine grinding activation, vacuum extrusion molding and low temperature consolidation is adopted. Through fine grinding of activator and iron-containing raw materials, optimization of ore matching, vacuum extrusion molding and low temperature drying consolidation with multifunctional binder, efficient molding and rapid consolidation of iron-containing furnace charge are formed.

Benefits of technology

It achieves efficient forming and rapid consolidation of iron-containing furnace charges, improves the compressive strength and reduction performance of the agglomerates, reduces the porosity, meets the performance requirements of blast furnace charges, and reduces the consumption of fossil energy.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing iron-containing furnace charge through vacuum extrusion forming and low-temperature consolidation, and belongs to the technical field of ferrous metallurgy. The method comprises the following steps: mixing an iron-containing raw material with an activating agent (containing iron ore powder, return mine and iron-containing dust), and carrying out fine grinding and activating treatment to obtain an activated iron-containing raw material; uniformly mixing the activated iron-containing raw material, iron ore concentrate, a binder (comprising metal iron powder, quick lime, water glass and silica sol) and water to obtain a mixture; carrying out vacuum extrusion molding on the mixture to obtain a wet block mass; according to the method, efficient forming and low-temperature rapid solidification of the iron-containing raw material can be achieved to form the block mass, and the formed block mass can meet the performance requirement of the blast furnace burden.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing an iron-containing furnace charge, and in particular to a method for preparing the iron-containing furnace charge by activating and pretreating part of the iron-containing raw materials, and subsequently optimizing ore blending, vacuum extrusion molding, and hot air drying and consolidation, belonging to the field of steel metallurgy. Background Art

[0002] my country's steel industry currently relies primarily on a long blast furnace-converter process. Fossil fuels account for approximately 85% of total steelmaking energy consumption, resulting in a high carbon emissions intensity per ton of steel produced. Carbon emissions from steel production are primarily concentrated in pre-iron processes, including coking, sintering, and pelletizing. Sintering and pelletizing processes contribute over 200 million tons of CO2 annually, representing over 15% of total CO2 emissions.

[0003] Cold briquetting involves adding a binder to iron-containing raw materials, pressing them into shape at room temperature, and then consolidating and hardening them at a lower temperature to produce briquettes that meet the requirements of subsequent smelting. Compared to sintering and pelletizing, this process avoids high temperatures and significantly reduces energy consumption and pollutant emissions.

[0004] There has been extensive research on cold briquetting both domestically and internationally. In 1899, Finland first used fine magnetite powder to produce cold-pressed iron ore pellets for blast furnace production. By around 1920, briquetting, as the only viable agglomeration method, had become widely used for forming iron ore fines and metallurgical dust. For example, at West Steel in Germany, cold-pressed pellets accounted for approximately 30–40% of the blast furnace charge. At Maxhütte, Germany, the blast furnace charge consisted entirely of cold-pressed pellets, made from fine iron ore, coke, and limestone. However, with the emergence and development of sintering, the limited production capacity of briquetting equipment became increasingly apparent, making it difficult to meet the large-scale production needs of the modern steel industry. Consequently, briquetting failed to achieve the significant development that sintering and pelletizing achieved. Cold-pressed iron ore pellets produced in my country are primarily used in small blast furnaces or as an auxiliary material in large blast furnaces. In 1988, Shanxi Nancun Iron Works used iron ore powder, coke powder and cement to produce cold-pressed pellets, which were successfully used in small blast furnace ironmaking. Research found that except for poor reducibility, other properties met the requirements. At the same time, Baotou Dongfeng Iron and Steel Works used Xiaoshetai iron concentrate as the main iron-containing raw material, added 10% cement as a binder, and produced cold-pressed pellets through a pelletizing disk and used them for 100m 3 Industrial trials in blast furnace smelting have shown that cold-consolidated pellets have good metallurgical properties, but the disadvantage is that the consolidation time is too long, and the strength of the pellets after seven days of natural curing is only 300N / P. Currently, the briquetting method is mostly used in rotary hearth furnace processes, where metallized pellets are produced by reducing metallurgical sludge from steel mills.

[0005] In recent years, with the increase of environmental protection pressure of the steel industry and the promulgation of the "double carbon" policy, the cold briquetting process with the advantage of low carbon dioxide emission has become a research hotspot again. At present, the cold briquetting process for preparing iron-containing blast furnace burden all has the shortcomings of poor performance of finished briquettes, long solidification time or introduction of many impurities. SUMMARY

[0006] In view of the above-mentioned defects existing in the existing cold briquetting process, the purpose of the present application is to provide a method for preparing iron-containing blast furnace burden by vacuum extrusion molding-low temperature solidification, which can realize efficient molding of iron-containing raw materials, low temperature rapid solidification to form briquettes, and the molded briquettes can meet the performance requirements of blast furnace burden.

[0007] In order to achieve the above technical purpose, the present application provides a method for preparing iron-containing blast furnace burden by vacuum extrusion molding-low temperature solidification, which comprises the following steps:

[0008] 1) mixing and finely grinding the iron-containing raw material with the activator to obtain an activated iron-containing raw material; the iron-containing raw material comprises iron ore powder, return fines and iron-containing dust;

[0009] 2) mixing the activated iron-containing raw material, iron concentrate with a binder and water to obtain a mixture; the binder comprises metallic iron powder, quicklime, water glass and silica sol;

[0010] 3) vacuum extrusion molding the mixture to obtain a wet briquette;

[0011] 4) drying and solidifying the wet briquette, and the method is completed.

[0012] The present application adopts the combined technical means of fine grinding activation, vacuum extrusion forming and low-temperature consolidation to realize efficient forming and rapid consolidation of iron-containing raw materials to obtain qualified iron-containing furnace charge. Specifically, first, an activator is used together with the iron-containing raw materials for fine grinding activation treatment. On the one hand, the fine grinding process can break up large-size particles, reduce the overall material particle size, and different iron-containing raw materials form different particle size distributions during the fine grinding process, achieving the purpose of regulating the particle size composition of the mixture. In the subsequent forming process, small-size material can fill the voids between large-size material, reducing the porosity of the briquette and increasing the cold briquette strength. At the same time, the fine grinding process can also make the particles irregular, and the irregular particles interlock with each other during the forming process, increasing the mechanical interlocking force between the materials, further reducing the porosity of the briquette and increasing the compressive strength. On the other hand, the activator is introduced in the fine grinding process, which interacts with the iron-containing raw materials during fine grinding, improving the surface properties of the granular material. The addition of the activator can effectively improve the hydrophilicity of the iron-containing material and has a certain binding effect, which can reduce the addition amount of the subsequent binder. Further, after the fine grinding activation pretreatment of the iron-containing raw materials, the plasticity of the mixture is improved, which is beneficial to vacuum extrusion forming. By using vacuum extrusion forming, the air content in the mixture is reduced during the forming process, further reducing the porosity. In addition, iron ore powder, return fines and iron-containing dust are used together, mainly based on the fact that the reducibility of natural iron ore is poorer than that of return fines. The reducibility of hematite in natural ore is good, while the reducibility of magnetite is poor. By optimizing the proportion of these iron-containing raw materials, the proportion of natural ore and return fines, and the proportion of magnetite and hematite can be adjusted, the reduction performance of the cold briquette can be improved, and the consumption of natural ore can be reduced. At the same time, during the preparation of the formed briquette from the iron-containing raw materials, a multifunctional binder containing metallic iron powder, quicklime, water glass and silica sol is used to realize the rapid forming and low-temperature efficient consolidation of the iron-containing furnace charge. The multifunctional binder plays a good binding role in the wet balling process, while in the drying and consolidation process, the quicklime in the binder will undergo carbonation consolidation, the metallic iron powder will undergo rusting consolidation, and the silica sol and water glass will harden and consolidate by losing water. The strength of the consolidated briquette can meet the requirements of different applications; and the chloride salt in the iron-containing solid waste can be used as a rusting agent for metallic iron powder to accelerate the rusting consolidation and further improve the briquette strength.

[0013] As a preferred scheme, the iron-containing raw material is composed of the following mass percentage components: iron ore powder 40%~50%, return fines 30%~40%, and iron-containing dust 10%~30%. By regulating the proportion of various iron-containing raw materials to optimize ore blending, the composition and physical and chemical properties of the cold-pressed briquettes can be met, and the requirements for cold-pressing can be met. In addition, the natural iron ore has relatively poor reducibility compared to the return fines, and the hematite in the natural ore has relatively good reducibility, while the magnetite has relatively poor reducibility. By optimizing the ore blending, the proportion of natural ore and return fines, and the proportion of magnetite and hematite, the reducibility of the cold-pressed briquettes can be improved. In addition, the iron-containing dust contains a large amount of chloride salts in addition to iron oxides, which can be used as a rusting agent to accelerate rusting and consolidation, further improving the strength of the briquettes. Therefore, by optimizing the proportion of iron ore powder, return fines, and iron-containing dust, iron-containing raw material briquettes with good reducibility and good consolidation effect can be obtained.

[0014] As a more preferred scheme, the iron ore powder is at least one of magnetite, hematite, and brown iron ore.

[0015] As a more preferred scheme, the return fines are at least one of sinter return fines and blast furnace return fines.

[0016] As a more preferred scheme, the iron-containing dust is at least one or more of sinter dust, blast furnace dust, converter dust, casthouse dust, iron oxide scale, and rolling mill sludge.

[0017] As a more preferred scheme, the content of chloride salts in the iron-containing dust is 0.1%~0.5%. The chloride salts contained in the iron-containing dust are beneficial to the preparation process of the iron-containing raw material briquettes. The chloride salts can be used as a rusting agent to accelerate rusting and consolidation, further improving the strength of the briquettes. The chloride salts are specifically, for example, potassium chloride and sodium chloride. If the content of chloride salts is too high, it will affect the normal operation of the blast furnace; if the content of chloride salts is too low, the rusting and consolidation effect is poor, and the strength of the briquettes is poor.

[0018] The purpose of the fine grinding and activation treatment of the present application is to further refine the iron-containing material with a particle size of <10 mm. Different iron-containing materials have different particle size distribution ranges under the same fine grinding conditions based on their different mineral compositions. For example, the particle size of the iron-containing dust is <3 mm. In the subsequent forming process, the iron-containing dust can fill the gaps between the relatively large-sized iron ore powder and return fines particles, reducing the porosity of the briquettes and increasing the strength of the cold-pressed briquettes.

[0019] As a preferred scheme, the activator is at least one of carboxymethyl cellulose, polyvinyl butyral, and polyacrylamide. The preferred activator can improve the surface properties of the iron-containing material, especially effectively improving the hydrophilicity of the iron-containing material, and can also have a certain binding effect.

[0020] As a preferred scheme, the mass of the activator accounts for 0.5% to 1.5% of the mass of the iron-containing raw material. If the mass of the activator is too low, the surface modification effect of the iron-containing raw material cannot be achieved; if the mass of the activator is too high, the viscosity of the material increases, which is not conducive to fine grinding and activation.

[0021] As a preferred scheme, the binder includes metallic iron powder, quicklime, water glass and silica sol. Further preferably, the binder is composed of the following components in percentage by mass: metallic iron powder 20% to 25%; quicklime 25% to 30%, water glass 20% to 25%, and silica sol 20% to 35%. The binder is a coupling effect of multiple binders, and can achieve rapid forming and low-temperature and high-efficiency consolidation of the iron-containing raw material. In the wet balling process, the binder plays a good binding role, and in the low-temperature drying process, the binder plays a high-efficiency consolidation role. In the drying and consolidation process, the quicklime will undergo carbonation consolidation, the metallic iron powder will undergo rusting consolidation, and the silica sol and water glass will harden and consolidate through water loss. The component ratio of the binder is optimized. If the content of the metallic iron powder is too high, the rusting consolidation process will be prolonged, affecting the production efficiency; if the content of the metallic iron powder is too low, the rusting consolidation effect will be poor, affecting the strength of the briquettes. If the content of the quicklime is too high, the carbonation consolidation process will be prolonged, affecting the production efficiency; if the content of the quicklime is too low, the carbonation consolidation effect will be poor, affecting the strength of the briquettes. If the content of the water glass is too high, the content of the introduced Na element will be high, affecting the normal operation of the blast furnace; if the content of the water glass is too low, the binding effect will be poor, affecting the strength of the briquettes. If the content of the silica sol is too high, the cost will be high; if the content of the silica sol is too low, the binding effect will be poor, affecting the strength of the briquettes. Therefore, the use of water glass and silica sol together can improve the consolidation effect and reduce the use cost. The modulus of the water glass is 2.5 to 4.1, and the solid content is 33% to 45%. The content of SiO2 in the silica sol is 25% to 40%.

[0022] As a preferred scheme, the mass percentage composition of the activated iron-containing raw material, iron concentrate and binder in the mixture is: 65% to 67%: 26% to 29%: 4% to 9%; the mass content of TFe in the mixture is > 57%, and the mass content of FeO is < 10%; and the mass content of water in the mixture is 6% to 9%. Since the average particle size of the activated iron-containing raw material is larger than that of the iron concentrate, if the proportion of the activated iron-containing raw material is too high or too low, the overall particle size of the mixture will be too large or too small, which is not conducive to forming.

[0023] As a preferred scheme, the iron concentrate is magnetite concentrate and / or hematite concentrate.

[0024] As a preferred scheme, the vacuum pressure of the vacuum extrusion forming is <-0.02 MPa. Through the vacuum extrusion forming, the air content in the mixture can be quickly reduced, and the purpose of rapid forming is achieved. And through the vacuum extrusion, the porosity can be effectively reduced, and the consolidation strength is improved.

[0025] As a preferred scheme, the wet briquetting shape is cylindrical, and the size is Φ15mm*15mm~Φ40mm*40mm.

[0026] As a preferred scheme, the drying and consolidation conditions are that the temperature is 100~250℃, and the time is 25~45min; the hot air drying method is adopted, and the CO2 volume content in the hot air is not less than 7%. The drying and consolidation process is clean and low-carbon, the hot air used can be low-temperature waste gas generated in the production process of a steel enterprise, and no fossil resources are consumed. The low-temperature waste gas in the steel enterprise, such as sintering trolley wind box branch pipe flue gas, large flue gas, and ring cooling machine hot waste gas and the like.

[0027] The fine grinding method used in the fine grinding and activation process of the application is one or a combination of roller grinding, ball grinding and wet grinding.

[0028] The drying equipment used in the wet briquetting of the application is a chain rake machine, a steel belt machine or a chain plate type drying machine.

[0029] The thickness of the wet briquetting layer is <350mm.

[0030] As a preferred scheme, the hot air used in the drying and consolidation process is from low-quality waste gas in a steel enterprise, is composed of one or more of sintering trolley wind box branch pipe flue gas, large flue gas and ring cooling machine hot waste gas, the temperature is 100~250℃, the CO2 content is not less than 7%, and the drying and consolidation time is 25~45min.

[0031] The method for preparing the iron-containing raw material provided by the application through vacuum extrusion forming-low temperature consolidation comprises the following specific steps:

[0032] (1) raw material pretreatment, adding 0.5% to 1.5% of the total weight of the iron-containing raw material of the activator in the iron-containing raw material, and fine grinding to obtain the activated iron-containing raw material. Among them, the iron-containing raw material is composed of 40% to 50% of iron ore powder, 30% to 40% of return ore, and 10% to 30% of iron-containing dust, and the particle size is <10mm; the iron ore powder is one or more of magnetite, hematite and limonite; the return ore is one or more of sinter return ore and blast furnace return ore; the iron-containing dust is one or more of sinter dust, blast furnace dust, converter dust, iron yard dust, iron oxide scale, and rolling sludge, with a particle size of <3mm, and the content of chloride salt (KCl, NaCl, etc.) in the iron-containing dust is 0.1% to 0.5%; the active additive is one or more of carboxymethyl cellulose, polyvinyl butyral, and polyacrylamide; the fine grinding method is one or more of roller grinding, ball grinding, and wet grinding.

[0033] (2) batching and mixing, the activated iron-containing raw material, iron concentrate and binder are batched and preliminarily mixed in a ratio of 65% to 67%:26% to 29%:4% to 9%; the iron concentrate is one or more of magnetite concentrate and hematite concentrate; the binder is composed of 20% to 25% of metallic iron powder, 25% to 30% of quicklime, 20% to 25% of water glass, and 20% to 35% of silica sol; after adding a certain proportion of water, further mixing to obtain a mixture with TFe>57%, FeO content <10%, and moisture content of 6% to 9%.

[0034] (3) vacuum extrusion forming, using a vacuum extruder to form the mixture into a wet briquette; the vacuum pressure during pressing is <-0.02MPa, and the shape of the formed briquette is cylindrical with a size of Φ15mm×15mm to Φ40mm×40mm.

[0035] (4) drying and consolidation, placing the wet briquette in a drying and consolidation device; the drying and consolidation device is one of a chain grate machine, a steel belt machine, and a chain plate dryer; the thickness of the wet briquette layer is <350mm; hot air is used for drying and consolidation, and the hot air used comes from low-quality waste gas in a steel enterprise, which is composed of one or more of sinter trolley windbox branch flue gas, large flue gas, and hot waste gas from the circular cooler, with a temperature of 100 to 250℃ and a CO2 content of not less than 7%, and the drying and consolidation time is 25 to 45min, to obtain a qualified iron-containing charge.

[0036] Compared with the prior art, the technical scheme of the present application has the following beneficial effects:

[0037] (1) In the preparation process of the iron-containing furnace charge of the present application, the iron-containing raw material is activated and pretreated, which can break large particles, reduce the particle size of the whole material, and regulate the particle size composition of the mixture. In the subsequent forming process, small particles can fill the gaps between large particles, reducing the porosity of the briquette and increasing the strength of the cold-pressed briquette. In addition, the particles become irregular, and the mechanical interlocking force between the particles increases during the forming process, further reducing the porosity of the briquette and increasing the compressive strength. On the other hand, the activator can improve the surface properties of the material, and the addition of active additives can effectively improve the hydrophilicity of the iron-containing material, and has a certain binding effect, which can reduce the addition amount of subsequent binders.

[0038] (2) In the preparation process of the iron-containing furnace charge of the present application, the iron-containing raw material is optimized, and by adjusting the ratio of each component, on the one hand, the composition and physical and chemical properties of the cold-pressed briquette can meet the requirements of cold-pressing, and on the other hand, the reducibility of natural iron ore is poorer than that of return ore, while the reducibility of hematite in natural ore is better, and the reducibility of magnetite is poorer. By optimizing the ore proportioning, the proportion of natural ore and return ore, and the proportion of magnetite and hematite can be adjusted, and the reducibility of the cold-pressed briquette can be improved. In addition, iron-containing solid waste and return ore can be disposed of, and the consumption of natural ore can be reduced.

[0039] (3) In the preparation process of the iron-containing furnace charge of the present application, vacuum extrusion is used for efficient forming. In the process of vacuum extrusion forming, the air content in the mixture is reduced, further reducing the porosity, and the plasticity of the mixture is improved after activation pretreatment, which is beneficial to vacuum extrusion forming. The vacuum extrusion forming process can also control the size of the briquette, which can meet the particle size requirements of different purposes.

[0040] (4) In the preparation process of the iron-containing furnace charge of the present application, a special binder is used to realize rapid forming and low-temperature efficient solidification. In the process of wet pellet preparation, the binder plays a good binding role, while in the drying and solidification process, the quicklime in the binder will undergo carbonation and solidification, the metal iron powder will undergo rustification and solidification, and the silica sol and water glass will harden and solidify by losing water. The strength of the solidified briquette can meet the requirements of different purposes; and the chloride salt in the iron-containing solid waste can be used as a rustification agent for metal iron powder, accelerating the rustification and solidification and further improving the strength of the briquette. In addition, the drying and solidification process is clean and low-carbon, and the hot air used is low-temperature waste gas generated in the production process of steel enterprises, which does not consume fossil resources.

[0041] In summary, by implementing the method of the present application, the compressive strength of the briquette is not less than 2500N / P, the tumbling index (+6.3mm) is not less than 78%, and the degree of reduction is not less than 70%. DETAILED DESCRIPTION

[0042] For the purpose of understanding the present application, the present application will be described in more detail by referring to preferred embodiments thereof below. However, the scope of the present application is not limited to the below specific embodiments.

[0043] Unless otherwise defined, all terms used in the description hereof are to be interpreted in the same way as those of a person skilled in the art. The patent terms used herein are only for the purpose of describing the preferred embodiments and are not intended to limit the scope of the present application.

[0044] Unless otherwise specified, the various reagents and raw materials used in the present application are commercially available products or products that can be prepared by known methods.

[0045] Example 1

[0046] 0.5% of carboxymethyl cellulose based on the total weight of the iron-containing raw material was added to the iron-containing raw material, and roller milling was performed to obtain an activated iron-containing raw material. The iron-containing raw material was composed of 40% magnetite concentrate, 30% sinter return fines, and 30% iron-containing dust, all having a particle size of <10 mm; the iron-containing dust was composed of 20% sinter dust and 80% mill scale, both having a particle size of <3 mm, and the content of chloride salts (KCl, NaCl, etc.) in the iron-containing dust was 0.2%. The activated iron-containing raw material, hematite concentrate, and binder were mixed in a ratio of 65%:26%:9% and were preliminarily mixed; the binder was composed of 20% metallic iron powder, 25% quicklime, 20% water glass, and 35% silica sol, the content of SiO2 in the silica sol was 31%, the modulus of the water glass was 4.0, and the solid content was 29%; after adding a certain proportion of water, further mixing was performed to obtain a mixture having a TFe content of 58%, an FeO content of 7.5%, and a moisture content of 7.5%. The mixture was subjected to vacuum extrusion using a vacuum extrusion machine to obtain cylindrical wet briquettes having a size of Φ15 mm x 15 mm, and the vacuum pressure during the pressing process was -0.04 MPa. The wet briquettes were placed on a chain grate machine for drying and solidification, and the thickness of the wet briquette layer was 330 mm; the flue gas from the tuyere branch pipes of sintering trolleys 1# to 5# was used for drying and solidification, the temperature was 150°C, the CO2 content was 7.5%, and the drying and solidification time was 40 min. The final cold pressed briquettes had a compressive strength of 2550 N / P, a tumbling index of 86%, and a degree of reduction of 76%.

[0047] Example 2

[0048] The polyacrylamide is added in the iron-containing raw material, and the ball milling is carried out, so as to obtain the activated iron-containing raw material. The iron-containing raw material is composed of 45% of hematite powder, 35% of sintered return fines and 20% of iron-containing dust, and the particle size is less than 10mm. The iron-containing dust is composed of 30% of blast furnace dust, 20% of iron tapping site dust and 50% of rolling steel sludge, and the particle size is less than 3mm. The content of chloride salt (KCl, NaCl, etc.) in the iron-containing dust is 0.15%. The activated iron-containing raw material, the magnetite concentrate and the binder are mixed according to the ratio of 65.5%:27%:7.5%, and the preliminary mixing is carried out. The binder is composed of 24% of metallic iron powder, 26% of quicklime, 25% of water glass and 25% of silica sol. The content of SiO2 in the silica sol is 28%, the modulus of the water glass is 2.8, and the solid content is 35%. After adding a certain proportion of water, the further mixing is carried out, so as to obtain the mixed material with the TFe of 58.5%, the FeO content of 8.8% and the water content of 8%. The vacuum extrusion machine is used to carry out the vacuum extrusion forming on the mixed material, so as to obtain the cylindrical wet briquetting, and the size is Φ30mm*25mm. The vacuum pressure in the pressing process is-0.06MPa. The wet briquetting is placed on the steel belt machine of the drying and solidification equipment, the thickness of the wet briquetting layer is 300mm, the mixed gas of the large flue gas and the hot exhaust gas of the ring cooling machine is used for drying and solidification, the temperature is 200℃, the CO2 content is 7.3%, and the drying and solidification time is 33min. After the application of the application, compared with example 1, the compressive strength of the cold-pressed briquetting is 2520N / P, the drum index is 84%, and the reduction degree is 78%.

[0049] Example 3

[0050] The polyvinyl butyral is added to the iron-containing raw material at 1.5% of the total weight of the iron-containing raw material, and the activated iron-containing raw material is obtained after grinding. The iron-containing raw material is composed of 40% magnetite powder, 40% blast furnace return fines and 20% iron-containing dust, and the particle size is <10mm; the iron-containing dust is composed of 10% sinter dust, 10% blast furnace dust and 80% iron oxide scale, and the particle size is <3mm; the content of chloride salt (KCl, NaCl, etc.) in the iron-containing dust is 0.35%. The activated iron-containing raw material, magnetite concentrate and binder are mixed according to the ratio of 66%:26%:8% and are preliminarily mixed; the binder is composed of 25% metallic iron powder, 30% quicklime, 20% water glass and 25% silica sol, the content of SiO2 in the silica sol is 35%, the modulus of the water glass is 2.5, and the solid content is 43%; after adding a certain proportion of water, the mixture is further mixed to obtain a mixture with TFe of 57.5%, FeO content of 9.2% and water content of 8.5%. The mixture is formed into cylindrical wet briquettes by using a vacuum extruder, and the size of the briquettes is Φ35mm×40mm, and the vacuum pressure during the pressing process is-0.08MPa. The wet briquettes are placed on the chain plate dryer, and the thickness of the wet briquette layer is 350mm; the mixed gas of the flue gas in the sintering trolley 1#-4# wind box branch pipe and the hot waste gas of the circular cooler is used for drying and solidification, the temperature is 250℃, the CO2 content is 8%, and the drying and solidification time is 28min. After using the present application, compared with example 2, the compressive strength of the final cold briquette is 2730N / P, the drum index is 87%, and the degree of reduction is 73%.

[0051] Comparative example 1

[0052] The carboxymethyl cellulose is added in the iron-containing raw material at 0.5% of the total weight of the iron-containing raw material to obtain the activated iron-containing raw material. The iron-containing raw material is composed of 40% of magnetite powder, 30% of sintered return fines and 30% of iron-containing dust, and the particle size is <10mm; the iron-containing dust is composed of 20% of sintered dust and 80% of iron oxide scale, and the particle size is <3mm; the content of chloride salt (KCl, NaCl, etc.) in the iron-containing dust is 0.2%. The activated iron-containing raw material, hematite concentrate and binder are mixed according to the ratio of 65%:26%:9% and are preliminarily mixed; the binder is composed of 20% of metallic iron powder, 25% of quicklime, 20% of water glass and 35% of silica sol, the content of SiO2 in the silica sol is 31%, the modulus of the water glass is 3.1, and the solid content is 37%; after adding a certain proportion of water, the mixture is further mixed to obtain the mixture with TFe of 58%, FeO content of 7.5% and water content of 7.5%. The vacuum extrusion machine is used to form the cylindrical wet briquettes with the size of Φ15mm×15mm, and the vacuum pressure during the pressing process is-0.04MPa. The wet briquettes are placed on the chain grate machine for drying and solidification, and the thickness of the wet briquette layer is 330mm; the flue gas in the air box branch pipes of sintering trolleys 1#-5# is used for drying and solidification, the temperature is 150℃, the CO2 content is 7.5%, and the drying and solidification time is 40min. Compared with the control example 1, the only difference is that the roller grinding is not performed, and the final cold pressed briquette has the compressive strength of 1850N / P, the drum index of 73% and the reduction degree of 77%.

[0053] Control Example 2

[0054] The iron-containing raw material is ball milled to obtain an activated iron-containing raw material. The iron-containing raw material is composed of 45% hematite powder, 35% sintered return fines and 20% iron-containing dust, all with a particle size <10 mm. The iron-containing dust is composed of 30% blast furnace dust, 20% taphole dust and 50% rolling mill sludge, all with a particle size <3 mm. The content of chloride salts (KCl, NaCl, etc.) in the iron-containing dust is 0.15%. The activated iron-containing raw material, magnetite concentrate and binder are mixed in a ratio of 65.5%:27%:7.5% and are preliminarily mixed. The binder is composed of 24% metallic iron powder, 26% quicklime, 25% water glass and 25% silica sol, with a SiO2 content of 28% in the silica sol and a modulus of 2.8 for the water glass. The solid content of the binder is 35%. After adding a certain proportion of water, the mixture is further mixed to obtain a mixture with a TFe content of 58.5%, an FeO content of 8.8% and a moisture content of 8%. The mixture is formed into cylindrical wet briquettes by using a vacuum extruder, with a size of Φ30 mm x 25 mm and a vacuum pressure of -0.06 MPa during the pressing process. The wet briquettes are placed on a steel belt machine for drying and solidification, with a wet briquette layer thickness of 300 mm. The mixed gas of flue gas and hot exhaust gas from the ring cooler is used for drying and solidification, with a temperature of 200°C and a CO2 content of 7.3%. The drying and solidification time is 33 min. Compared with Comparative Example 2, the only difference is that no activator is added in the pretreatment process. The cold briquette obtained finally has a compressive strength of 1700 N / P, a tumbling index of 68% and a degree of reduction of 79%.

[0055] Comparative Example 3

[0056] The polyacrylamide is added to the iron-containing raw material at 1% of the total weight of the iron-containing raw material, and ball milling is performed to obtain the activated iron-containing raw material. The iron-containing raw material is composed of 45% of hematite powder, 35% of sintered return fines and 20% of iron-containing dust, and the particle size is <10 mm; the iron-containing dust is composed of 30% of blast furnace dust, 20% of tapping channel dust and 50% of rolling steel sludge, and the particle size is <3 mm; the content of chloride salt (KCl, NaCl, etc.) in the iron-containing dust is 0.15%. The activated iron-containing raw material, magnetite concentrate and binder are proportioned at 65.5%:27%:7.5% and preliminarily mixed; the binder is composed of 34% of quicklime, 33% of water glass and 33% of silica sol, the content of SiO2 in the silica sol is 28%, the modulus of the water glass is 2.8, and the solid content is 35%; after adding a certain proportion of water, further mixing is performed to obtain the mixed material with TFe of 58.5%, FeO content of 8.8% and water content of 8%. The mixed material is subjected to vacuum extrusion molding using a vacuum extruder to obtain cylindrical wet briquettes with a size of Φ30 mm×25 mm, and the vacuum pressure during the pressing process is -0.06 MPa. The wet briquettes are placed on a steel belt machine of a drying and solidification device, the thickness of the wet briquette layer is 300 mm, and the mixed gas of large flue gas and hot exhaust gas of a ring cooler is used for drying and solidification, the temperature is 200 ℃, the CO2 content is 7.3%, and the drying and solidification time is 33 min. Compared with Example 2, the only difference of Comparative Example 3 is that the binder does not contain metallic iron powder, and the final cold pressed briquette has a compressive strength of 1960 N / P, a drum index of 74% and a degree of reduction of 72%.

[0057] Comparative Example 4

[0058] In the iron-containing raw material, 1.5% of polyvinyl butyral by weight of the total iron-containing raw material was added and ground, to obtain an activated iron-containing raw material. The iron-containing raw material was composed of 80% magnetite powder and 20% iron-containing dust, both having a particle size of <10 mm; the iron-containing dust was composed of 10% sinter dust, 10% blast furnace dust and 80% iron oxide scale, all having a particle size of <3 mm; the content of chloride salt (KCl, NaCl, etc.) in the iron-containing dust was 0.35%. The activated iron-containing raw material, magnetite concentrate and binder were mixed in a ratio of 66%:26%:8% and preliminarily mixed; the binder was composed of 25% metallic iron powder, 30% quicklime, 20% water glass and 25% silica sol, the content of SiO2 in the silica sol was 28%, the modulus of the water glass was 2.8 and the solid content was 35%; after adding a certain proportion of water, the mixture was further mixed to obtain a mixture having a TFe content of 57.5%, a FeO content of 9.2% and a water content of 8.5%. The mixture was subjected to vacuum extrusion using a vacuum extruder to obtain cylindrical wet briquettes having a size of Φ35 mm x 40 mm, and the vacuum pressure during the pressing process was -0.08 MPa. The wet briquettes were placed on a chain plate dryer, and the thickness of the wet briquette layer was 350 mm; the mixed gas of flue gas from sintering trolleys 1#-4# and hot waste gas from a circular cooler was used for drying and solidification, the temperature was 250°C, the CO2 content was 8% and the drying and solidification time was 28 min. Compared with Example 2, the only difference of Comparative Example 4 was that the return fines were not added by optimizing the ore proportioning, and the cold briquette obtained finally had a compressive strength of 2760 N / P, a drum index of 88% and a degree of reduction of 58%.

Claims

1. A method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation, characterized in that: The following steps are involved: 1) mixing an iron-containing raw material with an activator and performing fine grinding and activation treatment to obtain an activated iron-containing raw material; the iron-containing raw material comprises iron ore fines, return ore and iron-containing dust; 2) mixing the activated iron-containing raw material, the iron concentrate, a binder and water to obtain a mixture; the binder comprises metallic iron powder, quicklime, water glass and silica sol; 3) forming the mixture by vacuum extrusion to obtain a wet mass; 4) Dry and solidify the wet mass to obtain the product.

2. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to claim 1, characterized in that: The iron-containing raw material consists of the following components in percentage by mass: 40% to 50% of iron ore powder, 30% to 40% of returned ore, and 10% to 30% of iron-containing dust.

3. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to claim 2, characterized in that: The iron ore powder is at least one of magnetite powder, hematite powder and limonite powder; The returned ore is at least one of sintered returned ore and blast furnace returned ore; The iron-containing dust is at least one or more of sintering dust, blast furnace dust, converter dust, cast house dust, iron oxide scale, and steel rolling sludge; The mass content of chloride salt in the iron-containing dust is 0.1% to 0.5%.

4. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to claim 1, characterized in that: The activator is at least one of carboxymethyl cellulose, polyvinyl butyral and polyacrylamide.

5. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to any one of claims 1 to 4, characterized in that: The mass of the activator accounts for 0.5% to 1.5% of the mass of the iron-containing raw material.

6. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to claim 1, characterized in that: The binder is composed of the following components in percentage by mass: 20% to 25% of metallic iron powder, 25% to 30% of quicklime, 20% to 25% of water glass, and 20% to 35% of silica sol.

7. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to claim 1 or 6, characterized in that: The mass percentage composition of the activated iron-containing raw material, iron concentrate and binder in the mixture is: 65% to 67%: 26% to 29%: 4% to 9%; the TFe mass content of the mixture is greater than 57%, the FeO mass content is less than 10%, and the water mass content of the mixture is 6% to 9%.

8. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to claim 7, characterized in that: The iron concentrate is magnetite concentrate and / or hematite concentrate.

9. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to claim 1, characterized in that: The vacuum pressure of the vacuum extrusion molding is less than -0.02MPa; The wet mass is cylindrical in shape and has a size of Φ15mm×15mm to Φ40mm×40mm.

10. The method for preparing iron-containing furnace charge by vacuum extrusion molding and low-temperature consolidation according to claim 1, characterized in that: The drying and consolidation conditions are: temperature of 100-250° C., time of 25-45 min; hot air drying method is adopted, and the volume content of CO2 in the hot air is not less than 7%.